Unveiling the traits of HER2-low breast cancer: a comparative analysis of IHC1+ vs IHC2+/ISH-negative subgroups – insights from a 3-year cohort study - Correia, Jorge; Pulido, Catarina; Albuquerque, Joana; Prazeres, Gil; Margarido, Inês; Câmara, Mariana; Neto, Rita; Fernandes, Gonçalo; Godinho, João; Nave, Mónica; Mascarenhas, Francisco; Estudante, Isabel; et al. (Frontiers in Oncology, 2025)
BackgroundHalf of all breast cancer (BC) cases fall into the HER2-low category, defined as immunohistochemistry (IHC) 1+ or IHC 2+ in situ hybridization negative (ISH-). Two-thirds of these cases are IHC1+, while one-third is IHC2+/ISH-. New anti-HER2 antibody-drug conjugates (ADCs) have emerged as treatment options for metastatic or unresectable HER2-low BC patients. However, the heterogeneity between IHC1+ and IHC2+/ISH- subgroups and the clinical implications of varying HER2-low expression remain unclear.ObjectivesThis study aimed to compare demographic and clinicopathological differences between IHC1+ and IHC2+/ISH- subgroups and evaluate their response to neoadjuvant chemotherapy (NACT) in a cohort of patients with HER2-low BC.MethodsAll consecutive patients diagnosed with HER2-low invasive BC between 2018 and 2020 at our institution were included in this retrospective cohort study. Clinicopathological characteristics were compared between IHC1+ and IHC2+/ISH- subgroups. Pathologic complete response (pCR) rates were assessed in patients undergoing NACT, and a multivariable logistic regression model was used to identify factors associated with pCR.ResultsA total of 222 patients were included, evenly divided between IHC1+ (n=105, 47%) and IHC2+/ISH- (n=117, 53%) tumors, with no significant differences in baseline characteristics. Both subgroups predominantly comprised female patients (99% IHC1+ vs. 98% IHC2+/ISH-), postmenopausal (55% vs. 58%), with early-stage BC (94% vs. 98%) and estrogen receptor (ER)-positive tumors (90% vs. 90%). Around two-thirds had grade 2 tumors (63% vs. 64%), and the median Ki-67 index was 20% in both subgroups. Most BC were classified as luminal B-like (56% vs. 58%), followed by luminal A-like (35% vs. 34%), and TNBC (9% vs. 8%). Among the 43 patients with HER2-low BC who received NACT, 36% of IHC1+ patients achieved pCR, compared to only 5% in the IHC2+/ISH- subgroup (p = 0.021). Multivariable analysis revealed that IHC2+/ISH- status (vs. IHC1+) was significantly associated with lower odds of pCR (OR=0.07, 95% CI: 0.00–0.51, p = 0.025), while higher baseline Ki-67 and ER-negative status showed non-significant trends toward higher pCR rates after adjustment for other variables.ConclusionDespite similar clinicopathological features, IHC2+/ISH- status was independently associated with lower pCR rates compared to IHC1+. These findings suggest that HER2-low subgroups may influence response to NACT and should be considered in multivariable prediction models, potentially informing stratified treatment approaches in the era of anti-HER2 ADCs.